Ground deformation and source geometry of the 24 August 2016 Amatrice earthquake (Central Italy) investigated through analytical and numerical modeling of DInSAR measurements and structural‐geological data. Issue 24 (26th December 2016) - Lavecchia, G.; Castaldo, R.; de Nardis, R.; De Novellis, V.; Ferrarini, F.; Pepe, S.; Brozzetti, F.; Solaro, G.; Cirillo, D.; Bonano, M.; Boncio, P.; Casu, F.; et al.
Abstract: We investigate the ground deformation and source geometry of the 2016 Amatrice earthquake (Central Italy) by exploiting ALOS2 and Sentinel‐1 coseismic differential interferometric synthetic aperture radar (DInSAR) measurements. They reveal two NNW‐SSE striking surface deformation lobes, which could be the effect of two distinct faults or the rupture propagation of a single fault. We examine both cases through a single and a double dislocation planar source. Subsequently, we extend our analysis by applying a 3‐D finite elements approach jointly exploiting DInSAR measurements and an independent, structurally constrained, 3‐D fault model. This model is based on a double fault system including the two northern Gorzano and Redentore‐Vettoretto faults (NGF and RVF) which merge into a single WSW dipping fault surface at the hypocentral depth (8 km). The retrieved best fit coseismic surface deformation pattern well supports the exploited structural model. The maximum displacements occur at 5–7 km depth, reaching 90 cm on the RVF footwall and 80 cm on the NGF hanging wall. The von Mises stress field confirms the retrieved seismogenic scenario. Key Points: Investigation of the ground deformation and source geometry of the 2016 Amatrice earthquake (Central Italy) Coseismic displacements modeling through a 3‐D finite elements approach jointly exploiting DInSAR measurements and a 3‐D fault model Evidence of a bilateral rupture propagating along two en echelon normal faults conjoined at the hypocenter